For this case we have the following equation:
s = root (S.A / 6)
Substituting values we have:
For S.A = 180:
s = root (180/6)
s = root (30)
For S.A = 120:
s = root (120/6)
s = root (20)
s = root (4 * 5)
s = 2 * root (5)
Subtracting both values we have:
root (30) - 2 * root (5)
Answer:
root (30) - 2 * root (5)
option 2
Answer:
v=48
Step-by-step explanation:
![v=?\\\\u=12\\\\a=9\\\\t=4\\\\v=u+at\\\\v=(12)+(9)(4)\\\\v=12+36\\\\v=48](https://tex.z-dn.net/?f=v%3D%3F%5C%5C%5C%5Cu%3D12%5C%5C%5C%5Ca%3D9%5C%5C%5C%5Ct%3D4%5C%5C%5C%5Cv%3Du%2Bat%5C%5C%5C%5Cv%3D%2812%29%2B%289%29%284%29%5C%5C%5C%5Cv%3D12%2B36%5C%5C%5C%5Cv%3D48)
Answer:
S1 is congruent to S2
Step-by-step explanation:
Answer:
No solutions
Step-by-step explanation:
2(x+1)=2x+5
Expand the parentheses:
2x+2=2x+5
Subtract 2x from both sides:
2=5
Since this is not true, this equation has no solutions. Hope this helps!
Answer:
4/5 24/30
Step-by-step explanation: